Integration of Interactive Digital Media Based on Mbojo Folklore in Indonesian Language Learning to Improve Students' Reading and Writing Skills - Ikra Ikra; Syaiful Islami (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
This research is motivated by the low reading and writing skills of students in Indonesian learning, which is one of the crucial problems in education. The results of PISA 2018 show that Indonesia is ranked 74th out of 79 countries in reading literacy, indicating that there are still many students who have difficulty understanding, analyzing, and constructing texts effectively. This condition is exacerbated by the lack of contextual, interesting, and rooted learning media in local wisdom. Therefore, this research is important to develop learning solutions that integrate digital technology with local culture, especially Mbobo folklore, to meaningfully improve student literacy. The purpose of this research is to develop and test the effectiveness of interactive digital media based on Mbojo folklore in improving students' reading and writing skills. The research also contributes to enriching the Indonesian learning model based on culture and technology. The method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, which is applied from needs analysis to media evaluation. The results showed a significant improvement in reading and writing skills with an average increase of 28.8%. In addition, student satisfaction reached 85% and active engagement was 82%. These findings confirm that interactive digital media based on Mbojo folklore is effective in increasing literacy while strengthening students' connection to local culture.